TRADISI NUGAL SUKU DAYAK DI KUTAI BARAT SEBAGAI KONTEKSTUALISASI PENGAJARAN ALKITAB - Samderubun, Wilhelmus Patrisio; Rogo Yuono, Yusup; Sugiyarto, Iskak (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2024)
Nugal is a tradition of planting rice in the fields in cooperation owned by the Dayak tribe. In the spiritual context, this tradition has a focus on spiritual involvement and religious meaning in agricultural activities involving the community, so in this case the research aims to understand the biblical values and also the philosophical meaning of the tradition. Through participatory observation, informal interviews, and literature studies as part of qualitative methods, the author explores the nugal tradition to draw deep meaning in it. The findings show that Dayak farming activities are not just an economic practice, but it is also loaded with noble values that strengthen community solidarity. A deep understanding of the religious dimension in the Dayak Nugal tradition provides valuable insights to develop contextual theology relevant to local cultural realities.